2014
DOI: 10.1111/jan.12360
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review investigating the effectiveness of Complementary and Alternative Medicine (CAM) for the management of low back and/or pelvic pain (LBPP) in pregnancy

Abstract: There is limited evidence supporting the use of general CAM for managing pregnancy-related low back and/or pelvic pain. However, the restricted availability of high-quality studies, combined with the very low evidence strength, makes it impossible to make evidence-based recommendations for practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 51 publications
0
48
0
Order By: Relevance
“…Recent evidence suggests there has been growth in CAM approaches for non-medical management of various perinatal symptoms and conditions, including nonpharmacologic alternatives for nausea/vomiting, pain management, or labor induction (Close et al, 2014; Kozhimannil, Johnson, Attanasio, Gjerdingen, & McGovern, 2013; Matthews, Haas, O’Mathuna, Dowswell, & Doyle, 2014). Since many non-medical approaches to managing aspects of pregnancy and childbirth are self-prescribed, baseline information is needed to understand whether and how women are using CAM therapies in combination with or in lieu of conventional medicine for pregnancy-related conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests there has been growth in CAM approaches for non-medical management of various perinatal symptoms and conditions, including nonpharmacologic alternatives for nausea/vomiting, pain management, or labor induction (Close et al, 2014; Kozhimannil, Johnson, Attanasio, Gjerdingen, & McGovern, 2013; Matthews, Haas, O’Mathuna, Dowswell, & Doyle, 2014). Since many non-medical approaches to managing aspects of pregnancy and childbirth are self-prescribed, baseline information is needed to understand whether and how women are using CAM therapies in combination with or in lieu of conventional medicine for pregnancy-related conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The Australian national survey found that 34 percent of women consulted massage therapists during their pregnancies (38). Osteopathic and chiropractic manipulation also had a low rate of use in our sample (10%) despite its relative safety in pregnancy (39) and evidence supporting its effectiveness for pregnancy-related back pain (26). Osteopathic and chiropractic manipulation also had a low rate of use in our sample (10%) despite its relative safety in pregnancy (39) and evidence supporting its effectiveness for pregnancy-related back pain (26).…”
Section: Discussionmentioning
confidence: 69%
“…While some therapies such as yoga and massage may be beneficial for stress, wellness, and pain reduction (25,26), other modalities may be harmful (27,28). Clinicians who provide preconception counseling or obstetrical care should be aware of the patterns of CAM use among women of childbearing age so that they may direct care toward therapies known to be safe and effective.…”
mentioning
confidence: 99%
“…The drawback of these acupuncture applications was the need for specialized personnel and the restricted access to treatment, in relation to the frequency of appearance of this condition. 2,12,13 Only one study has evaluated the results of ear acupuncture in pregnant women; this was conducted in the USA and in a hospital environment and reported that the insertion of needles in the ear over a period of 1 week reduced the pain and disability experienced by pregnant women with LBPGP. 14 The aim of the present study was to assess the efficacy of acupuncture in reducing the pain experienced by pregnant women in the lower back and/or the posterior pelvic girdle.…”
Section: Introductionmentioning
confidence: 99%